Exploring the Role of Music Students' Negative Emotions on AI Readiness and Engagement in Music Learning in Indonesia - Bastian Hutagaol; Deden Haerudin; Hery Budiawan (International Journal of Educational Technology and Society, 2025)
This study explores the role of negative emotions—such as anxiety, frustration, and self-doubt—on music students' readiness to adopt artificial intelligence (AI) technologies and their engagement in music learning in Indonesia. Against the backdrop of rapid AI integration in education, the research investigates how these emotions mediate the relationship between AI readiness and student engagement. Using a quantitative approach with structural equation modeling (SEM), data were collected from 500 music students across five Indonesian higher education institutions. The findings reveal that negative emotions significantly influence both AI readiness and engagement levels, highlighting the need for emotional awareness in pedagogical practices. The study contributes to the development of strategies that support students' emotional well-being while fostering their adaptability to AI-driven learning tools, ensuring a holistic and inclusive future for music education.